Mild Traumatic Brain Injury Evokes Pyramidal Neuron Axon Initial Segment Plasticity and Diffuse Presynaptic Inhibitory Terminal Loss - Michal Vascak; Jianli Sun; Matthew Baer; Kimberle M. Jacobs; John T. Povlishock (Frontiers in Cellular Neuroscience, 2017)
The axon initial segment (AIS) is the site of action potential (AP) initiation, thus a crucial regulator of neuronal activity. In excitatory pyramidal neurons, the high density of voltage-gated sodium channels (NaV1.6) at the distal AIS regulates AP initiation. A surrogate AIS marker, ankyrin-G (ankG) is a structural protein regulating neuronal functional via clustering voltage-gated ion channels. In neuronal circuits, changes in presynaptic input can alter postsynaptic output via AIS structural-functional plasticity. Recently, we showed experimental mild traumatic brain injury (mTBI) evokes neocortical circuit disruption via diffuse axonal injury (DAI) of excitatory and inhibitory neuronal systems. A key finding was that mTBI-induced neocortical electrophysiological changes involved non-DAI/ intact excitatory pyramidal neurons consistent with AIS-specific alterations. In the current study we employed Thy1-yellow fluorescent protein (YFP)-H mice to test if mTBI induces AIS structural and/or functional plasticity within intact pyramidal neurons 2 days after mTBI. We used confocal microscopy to assess intact YFP+ pyramidal neurons in layer 5 of primary somatosensory barrel field (S1BF), whose axons were continuous from the soma of origin to the subcortical white matter (SCWM). YFP+ axonal traces were superimposed on ankG and NaV1.6 immunofluorescent profiles to determine AIS position and length. We found that while mTBI had no effect on ankG start position, the length significantly decreased from the distal end, consistent with the site of AP initiation at the AIS. However, NaV1.6 structure did not change after mTBI, suggesting uncoupling from ankG. Parallel quantitative analysis of presynaptic inhibitory terminals along the postsynaptic perisomatic domain of these same intact YFP+ excitatory pyramidal neurons revealed a significant decrease in GABAergic bouton density. Also within this non-DAI population, patch-clamp recordings of intact YFP+ pyramidal neurons showed AP acceleration decreased 2 days post-mTBI, consistent with AIS functional plasticity. Simulations of realistic pyramidal neuron computational models using experimentally determined AIS lengths showed a subtle decrease is NaV1.6 density is sufficient to attenuate AP acceleration. Collectively, these findings highlight the complexity of mTBI-induced neocortical circuit disruption, involving changes in extrinsic/presynaptic inhibitory perisomatic input interfaced with intrinsic/postsynaptic intact excitatory neuron AIS output.